Hospitalized After Medical Readiness for Discharge: A Multidisciplinary Quality Improvement Initiative to Identify Discharge Barriers in General Medicine Patients. (January 2020) - Meo, Nicholas; Liao, Joshua M.; Reddy, Ashok
Reducing the length of hospitalization is a shared priority for patients, clinicians, and other health care stakeholders. However, patients can remain hospitalized after being "medically ready" for discharge, accumulating delayed discharge bed days (DDBDs). As part of a quality improvement initiative, the authors developed a method to measure DDBD and define discrete barriers to discharge identified by inpatient clinicians. Patients with delayed discharge had a higher rate of in-hospital complications compared to those who were discharged routinely. To identify modifiable barriers among patients with delayed discharges, 2 patient subgroups were defined: prolonged hospitalization (>19 DDBDs, top quintile accumulated) and extended hospitalization (≤19 DDBDs). Patients with prolonged hospitalization were more likely than those with extended hospitalization to have financial ( P < .001) or behavioral ( P < .001) barriers, homelessness ( P < .05), and impairment of decision-making capacity ( P < .01). Understanding the characteristics and discharge barriers of patients who are hospitalized despite medical readiness may increase appropriateness of inpatient resources.